Hubungan Kecemasan dan Komplikasi Kehamilan dengan Kesiapan Ibu Hamil Trimester III Menghadapi Persalinan di Wilayah Kerja Puskesmas Benteng - Harmawati Rustan (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
The third trimester of pregnancy is a challenging period since pregnant women experience various physical and psychological changes that can affect their readiness for childbirth. High anxiety levels and the presence of pregnancy complications are known to reduce maternal preparedness for labor. This study aims to determine the relationship between anxiety levels and pregnancy complications with the readiness of third trimester pregnant women in facing childbirth in the working area of Benteng Community Health Center, Selayar Islands Regency. This research used a quantitative approach with a correlational design and a cross-sectional method. The population consisted of all third trimester pregnant women, with a total sample of 86 respondents selected using purposive sampling. The research instruments included an anxiety questionnaire using the Hamilton Anxiety Rating Scale (HARS), a pregnancy complication checklist, and a childbirth readiness questionnaire. Data were analyzed using the Chi-Square test and multiple logistic regression at a significance level of α = 0.05. The results of the study showed no significant relationship between anxiety and readiness for childbirth (p < 0.550) or between pregnancy complications and readiness for childbirth (p < 0.690). Therefore, it can be concluded that anxiety and pregnancy complications are not significantly related to the readiness of pregnant women in the third trimester for childbirth. This indicates that maternal readiness is influenced by factors other than the variables studied, such as knowledge, family support, and previous childbirth experiences.